Harmonization of International Patient Law in Biotechnology: Strategies For Enhancing Innovation And Global Access - Raymond R. Tjandrawinata; Henry Soelistyo Budi (Dinasti Research, 2025)
The fragmented global patent landscape poses significant challenges for biotechnology, one of the most innovative sectors of the 21st century. Despite the potential to revolutionize healthcare and agriculture, differences in patent regulation between jurisdictions impede progress, limit equitable access to therapies, and complicate international collaboration. This paper examines the key regulatory frameworks in the United States, the European Union, Japan, and China, focusing on the inherent strengths and challenges of each, by analyzing case studies, such as CRISPR gene editing and CAR-T therapy. The article identifies strategies to deal with ethical dilemmas, intellectual property rights differences, and cross-border enforcement issues. The analysis in this publication encourages harmonization initiatives through regional agreements, international dialogue, and open innovation models to promote global access and sustainable innovation.